Analysis of Content Marketing and Online Advertising on Brand Awareness for Halal Skincare Products Brands - Yulia Nur Hasanah; Fauzan Aziz (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: Nowadays all companies utilize the development of information and communication technology to increase interaction with consumers because consumers can obtain information quickly through digital media. Therefore, all companies are competing to create marketing content and utilize all digital media to create online advertisements to help their brand can be recognized by consumers. So, this research aims to analyze the impact of content marketing and online advertising on brand awareness for halal skincare product brands in Indonesia.Methodology: This research uses descriptive causality research and three variables, namely content marketing, and online advertising, and brand awareness. The data in the research was collected using questionnaires with 385 respondents and processed using Partial Least Square (PLS). The hypothesis testing using the F-test and coefficient of determination.Finding: It found a positive impact of content marketing and online advertising on brand awareness, both partially and simultaneously. Furthermore, content marketing and online advertising have an impact of 91.20% on brand awareness.Conclusion: According to the findings content marketing and online advertising can increase brand awareness both particularly and simultaneously.